2021
DOI: 10.1101/2021.05.03.442423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correction of amblyopia in cats and mice after the critical period

Abstract: Monocular deprivation early in development causes amblyopia, a severe visual impairment. Prognosis is poor if therapy is initiated after an early critical period. However, clinical observations have shown that recovery from amblyopia can occur later in life when the non-deprived (fellow) eye is removed. The traditional interpretation of this finding is that vision is improved by relieving interocular suppression in primary visual cortex. However, an alternative explanation is that elimination of activity in th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Just as an inactive muscle fiber rapidly recovers size when the temporarily silenced motoneuron activity is restored, we wondered if dLGN cell size changes ascribed to reduced retinal activity is similarly transient. In previous studies, we demonstrated that felloweye retinal inactivation applied at 10 weeks of age can promote recovery from the effects of a prior long-term MD, and critically the inactivation produced no lasting detriment to the inactivated eye or to the dLGN layers connected to it (Duffy et al, 2018; Fong et al, 2021; DiCostanzo et al, 2020). We were therefore interested to test the durability of the effect of retinal inactivation by providing a subset of animals with binocular vision after they received 10 days of retinal inactivation applied at 10 weeks of age.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…Just as an inactive muscle fiber rapidly recovers size when the temporarily silenced motoneuron activity is restored, we wondered if dLGN cell size changes ascribed to reduced retinal activity is similarly transient. In previous studies, we demonstrated that felloweye retinal inactivation applied at 10 weeks of age can promote recovery from the effects of a prior long-term MD, and critically the inactivation produced no lasting detriment to the inactivated eye or to the dLGN layers connected to it (Duffy et al, 2018; Fong et al, 2021; DiCostanzo et al, 2020). We were therefore interested to test the durability of the effect of retinal inactivation by providing a subset of animals with binocular vision after they received 10 days of retinal inactivation applied at 10 weeks of age.…”
Section: Resultsmentioning
confidence: 78%
“…It is worth pointing out that the restoration of normal dLGN soma size and the recovery of VEPs after inactivation occurred at an age (i.e. 10 weeks old) when inactivation of the fellow eye can promote full recovery from the anatomical and physiological effects of long-term MD (Duffy et al, 2018; Fong et al, 2021). The current findings indicate that the modifications elicited by inactivation do not to have a lasting negative impact on the visual system, and instead appear to elicit a constellation of modifications that avail an opportunity for recovery from the neural modifications provoked by amblyogenic rearing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Depression of deprived inputs occurs at a synaptic level and outlasts the perturbation. On the other hand, the same peripheral perturbation in adults does not induce a rapid decrease in response strength, although potentiation of the intact input does proceed 4,5 . Furthermore, in the young, the impact of deprivation on excitatory neuron activity levels is compensated for by a decrease in evoked inhibitory neuron activity.…”
Section: Introductionmentioning
confidence: 92%